Saneamiento tipo Terra Preta de biosólidos obtenidos a partir de sanitarios ecológicos secos - Ubau-Piedra, Stephanie Estrella (Instituto Tecnológico de Costa Rica, 2019)
In Costa Rica, 75% of the sources of drinking water supply are threatened by nitrate and wastewater contamination, mainly from agricultural agrochemicals and septic tanks, respectively. The use of dry ecological toilets affects both issues, by eliminating the use of water to carry away excreta, which eliminates the need for septic tanks and provides biosolids that, when treated correctly, provide a soil improver which can substitute agrochemicals. The treatment of sanitation Terra Preta (TPS), whose purpose is to obtain a substrate like the black soil of the Amazon is an adequate treatment for biosolids. In the present work, the sanitation of biosolids from a dry ecological sanitation in the Santos area was carried out. The system composed of a lactic acid fermentation (FAL) and a vermicomposting, produces an improvement in the physical and chemical characteristics; as well as an inhibition of pathogens in the treated biosolid. The initial biosolid with a C / N ratio of 12.53, a pH of 6.7 and pF of 4.15 with the presence of Salmonella, to which TPS was applied, obtaining a soil improver of pathogens free of pH 6.52 and C / N ratio of 12.25. This was applied as a soil improver in lettuce in concentrations of 4,4% v / v causing almost 4 times greater growth of dry weight to the plants that were not subjected to the application of the substrate and 1.5 times greater of dry weight to the plants. plants treated with a commercial fertilizer after 3 weeks of growth.
Proyecto Final de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química,2019
Keywords: Terrapreta; Fermentación; Ácido; Servicios ambientales